The Existence of an Intra-Amniotic Microbiome: Assessing a Controversy - Kumar Uddipto; Julie A. Quinlivan; George L. Mendz (Biology)
The existence of intra-amniotic and placental microbiomes during pregnancy has been the source of considerable debate, with research yielding conflicting evidence. This study evaluated investigations into the putative presence of these microbiomes in healthy pregnancies by identifying design and data interpretation issues, particularly concerning contamination in samples with low-density bacterial DNA. Positive findings from diverse populations suggest a consistent presence of microbiota in the intra-amniotic space. Negative conclusions regarding the existence of these prenatal microbiomes emphasise the impact of contamination in the analysis of samples with low-density bacterial DNA. This study concluded that there is no definitive evidence to refute the existence of intra-amniotic microbiomes in healthy pregnancies. Also, it provides suggestions for controlling potential contamination factors in future research on intra-amniotic and placental microbial populations.